KONSEP DAN REGULASI TV LOKAL DALAM KERANGKA PENGUATAN BUDAYA LOKAL - Handrini Ardiyanti (Jurnal Politica, 2011)
Local television have an important roles in maintaining local culture, but in reality, their format have no different from other commercial television which are more like to show the global culture. Therefore, this paper attempted to answer questions about how the broadcasting regulation influences local television. In its conclusion, this paper explains how local television should be established as public broadcasting so they can strengthen the local culture through their programs.